Features of Psychosomatic Symptoms in the Health Profile of Students - O. B. Polyakova; T. I. Bonkalo (Здоровье мегаполиса, 2024)
Introduction. Professional training of future specialists involves not only acquisition of knowledge, skills and abilities and development of professionally important qualities, but also prevention of somatoform disorders among students that is understood as a tendency to feel, experience and report the presence of educational and professional stress in the form of physical symptoms, in particular, symptoms of anxiety. Leveling out psychosomatic symptoms that negatively affect the skin, respiratory, digestive, cardiovascular, and musculoskeletal systems of students will serve as the basis for a psychological prevention program.Purpose. The goal was to identify the features of psychosomatic symptoms in the health profile of students.Methods and materials. A total of 654 adult students from Moscow universities participated in the study on a voluntary basis. In order to identify health conditions and physical symptoms reflecting the response to negative factors and hidden emotions, the participants were asked to fill out two questionnaires: “How healthy are you?” elaborated by O.P. Novykh and “Psychosomatics of our life,” developed by I.K. Odintsov. Then, the data were processed using the Pearson correlation coefficient and the Chaddock scale.Results. The following features of psychosomatic symptoms were revealed: average health condition characterized by an above-average level of disorders of the digestive system and negative skin reactions; average level of disorders of the cardiovascular system and general somatization indicators; below-average level of disorders of the respiratory system and the musculoskeletal system.